Women and Medical Knowledge in the 1950's: A Study of the Process of Social Construction - Findlay, Ann Deborah (My University, 1990)
This study examines how medical knowledge of women is socially informed in historically specific contexts. The case of obstetric and gynecologic knowledge of the 1950s is the focus of this investigation of the social character of medical knowledge.
There is a prevalent notion that error results when medical knowledge is socially influenced. However, in the present work, social influence is seen as involved in the production of all medical knowledge. Thus, the present study offers an alternative conceptualization to dualist models where the medical and the social realms are considered separate entities. In such models, social influences are posited as factors external to medical knowledge. Rather, it is suggested here that the production of medical knowledge of women is a process consistently informed by its social context.
The social production of medical knowledge is indicated by the ways in which professional concerns, social notions of women and gender relations, and the socio-political context were employed as resources in the construction of obstetric and gynecologic knowledge during the 1950s. The technical distinctions made in that knowledge of women's reproductive health arose out of the social resources available to the medical profession in that postwar period. Social concepts of femininity and domesticity are resources displayed in the categorizations of medical normality and pathology generated or accepted by 1950s obstetricians and gynecologists.
The form and content of obstetric and gynecologic knowledge, then, reveal how medical, technical terminology acted as a rhetorical strategy. This strategy allowed decisions to be made about norms and to be presented as neutral and asocial. However, the present research suggests that obstetric and gynecologic knowledge was inherently social in its production and maintenance.
Keywords: Sociology; Sociology